The Effect of Acupressure Massage (At Points SP 6, LI 4, and ST 36) on Primary Menstrual Pain in Adolescent Girls at SMP N 6 Payakumbuh City - Pitri, Zilfi Yola; Nataria, Desti; Felina, Mutia; Hidayati, Lisa (JURNAL IBU DAN ANAK, 2023)
One way to relieve pain non-pharmacologically is with Accrued Massage which can stimulate the formation of endorphin hormones. The purpose of this study was to determine the effect of acupressure massage (at points SP6, LI4, and ST36) on primary menstrual pain in adolescent girls at SMP N 6 Kota Payakumbuh. This study used a quasi-experimental method with one group pre-post test design. population of 16 people using Accidental sampling technique, obtained a sample of 12 respondents. The sampling technique uses observation sheets. Furthermore, Shapiro Wilk normality statistical tests were carried out with the results of normal undistributed data. Thus bivariate analysis uses the Wilcoxon test. The results of the study found the average scale of menstrual pain before Acupressure Massage was 4.25. Meanwhile, after acupressure massage, symptoms were reduced with an average number of 0.25. From the results of the p value test, the result p = 0.002 where p <0.05. It can be concluded that acupressure has an effect on reducing menstrual pain.